Peer Approach in Developing Resistance Skills on Drugs Among Adolescents - Duka-Pante, Francis Grace H. (Alipato, A Journal of Basic Education, 2010)
The Philippines is currently experiencing a “youth bulge.” In fact, the 2000 Census counted 15.1 million adolescents comprising 19.7% of the total population. It is estimated to reach 30 million in 2030 (Berja & Ojena, as cited in Cruz & Raymundo, 2004).  The population of Filipino adolescents poses a great health concern not only because of their big number but also of their vulnerability to risk-taking behaviors. To prove this, the Young Adult Fertility and Sexuality Study (YAFS III) conducted by the University of the Philippines Population Institute in 2002 revealed alarming statistics. It reported that of the 15-24 year-old age group, 21% smoke, 42 % drink, and 2.8% use drugs (Cruz & Raymundo, 2004). Various research studies have shown the crucial role of peers in adolescent health and development. An example is that a peer group can lead the adolescent down the road of vice (Gastardo-Conaco, Jimenez, & Billedo, 2003).  A study which explored the role of peers in drinking behavior reported that the need to fit in the peer group is the primary reason why most young people start drinking alcoholic beverage and try illegal substance (Neuwirth & Frederick, 2004). Considering the strong influence of peers in the adolescents’ life and identifying peer pressure as one of the causes for the risk-taking behaviors among the youth, this study was undertaken to determine how could peers be the source of positive influence and a part of the adolescents’ health support system. Peer approach is a program strategy designed to train select members of any group of equals to effect change among members of that same group. It seeks to utilize the positive aspects of adolescent peer groups by helping them learn from each other (UNESCO, 2003).